A new species of Crossodactylodes (Anura: Leptodactylidae) from Minas Gerais, Brazil: first record of genus within the Espinhaço Mountain Range - Barata, Izabela M.; Santos, Marcus T.t.; Leite, Felipe S.f.; Garcia, Paulo C.a. (Zootaxa, 2013)
The genus Crossodactylodes comprises three species of Atlantic Rainforest endemic frogs strictly dependent on bromeliads where they spend their entire life cycle. The current geographic distribution of the genus covers highland areas of Atlantic Rainforest in the States of Rio de Janeiro and Espírito Santo, Southeastern Brazil. We describe a new species of the genus from Parque Estadual do Pico do Itambé, at Santo Antônio do Itambé municipality, State of Minas Gerais, Southeastern Brazil. Crossodactylodes itambe sp. nov. is characterized by the following combination of traits: male SVL 16.2 ± 1.3 (14.0–17.6 mm, n = 10), female SVL 16.2 ± 1.0 (13.5–18.0 mm, n = 15); snout short, rounded in dorsal view, sloping in lateral view; absence of vocal sac and vocal slits in males; absence of vomerine teeth; males with upper arms and forearms hypertrophied; cloacal flap prominent, simple; dorsal skin coarsely granular. The new species inhabits rupicolous bromeliads in open areas of rocky fields, and is recorded in altitudes between 1836 and 2062 m above sea level. This record extends the genus distribution for about 325 km northwest from where it was known. Crossodactylodes sp. nov. is the only species of the genus that occurs in open field habitats (campos rupestres), in very high altitudes of a non-costal mountain range (the Espinhaço Range).